Perancangan Aplikasi dalam Monitoring Absensi Siswa pada SDN 060941 Menggunakan QR Code Berbasis Android - Ibnu Thariq Hasibuan; Silvia Lestari (TAMIKA: Jurnal Tugas Akhir Manajemen Informatika & Komputerisasi Akuntansi, 2025)
Student attendance is an essential aspect in supporting discipline and the effectiveness of the teaching and learning process at schools. However, the manual attendance system currently used at SDN 060941 often leads to several issues, such as delayed recording, data loss risks, and difficulties in monitoring student presence in real time. Therefore, this study designs an Android-based attendance monitoring application utilizing QR Code technology. The application allows students to record their attendance by scanning the provided QR Code, enabling attendance data to be automatically stored and integrated into the database. The system development method applied in this research is the waterfall model, which includes requirements analysis, design, implementation, and testing. The results show that this application can improve the efficiency of attendance processes, minimize recording errors, and provide convenience for the school in monitoring student presence in a fast, accurate, and structured manner.